Analisis Organizational Citizen Behavior (OCB) dan Komitmen Orginisasi terhadap Kinerja Pegawai Sdm PT Pelindo Multi Terminal Di Medan Dengan Self Efficacy Sebagai Variabel Intervening - Satriawan, Deny; Darmilisani; Siswa Pratama (Journal of Community Research and Service, 2025)
The purpose of this study is to find out organizational citizen behavior (OCB), organizationalcommitment and self efficacy affect employee performance, to find out organizational citizen behavior (OCB)and organizational commitment affect self efficacy, to find out organizational citizen behavior (OCB) affectsemployee performance through self efficacy, and to find out whether organizational commitment affects employeeperformance PT Pelindo Multi Terminal through self efficacy. The population in this study is 178 employeesworking at PT Pelindo Multi Terminal. The sample in the study was 64 employees taken using the slovin formula.The data collection technique used in this study was carried out by distributing questionnaires. The analysistechnique in the study uses SmartPLS (Partial Least Square) starting from model measurement (outer model),model structure (inner model) and hypothesis testing. The results of the study show that organizational citizenbehavior (OCB), commitment to organization and self efficacy affect employee performance, organizationalcitizen behavior (OCB) and commitment to organization affect employee performance, organizational citizenbehavior (OCB) affects employee performance through self efficacy and commitment to organization affects theperformance of HR employees of PT Pelindo Multi Terminal through self efficacy.